Model Pembelajaran Problem Based Learning untuk Mencerdaskan Partisipasi Sosial Peserta Didik Kelas III Sekolah Dasar - Yanti, Yuli; Astuti, Dwi; Hidayah, Nurul (Universitas Islam Negeri Raden Fatah Palembang, 2024)
Educator Already use several learning models, but participant social intelligence educated still low. Research This aiming for known influence significant Problem Based model Learning to intelligence social participant educate class III SDN Ancient Sacred. Study This is study quantitative with approach Quasi Experiment with design Pretest and Posttest Control Group Design. Population study This is participant educate Class III at SDN Negeri Purbasakti. Sample study This that is all amount population consisting of from class IIIA and IIIB Sampling Techniques Which used is Purposive Sampling with amount 57 participant educate. Technique data collection using questionnaire. Data analysis test in study This using the T-Test. while for see improvement from pre-test to post-test using the N-Gain test. Based on results research and discussion can concluded that based on hypothesis that has been formulated previously so can know that mark t count < t table = 0.000 < 0.05. With This H1 is accepted and H0 is rejected. So can concluded that there is influence in a way significant between learning model Problem Based Learning towards intelligence social participant educate class III SDN Country Ancient Sacred Lampung North. Problem Based Learning significantly affects students' social intelligence, this finding can be used as a basis for integrating Problem Based Learning in the school curriculum, especially for subjects that require collaboration or problem solving.